Finite element based fatigue life prediction of cylinder head for two-stroke linear engine using stress-life approach - Rahman , M.M.; Hamada, Khalaf I; Noor, M.M.; Bakar, Rosli A.; Kadirgama, K.; Maleque, Md. Abdul (Asian Network for Scientific Information, 2008)
Abstract: This describes the finite element based fatigue life prediction of cylinder head for two-stroke linear engine subjected to variable amplitude loading applicable to electric power generation. A set of Al-alloys, cast iron and forged steel for cylinder head are considered in this study.